Assessment Practices for Children with Autism Spectrum Disorder in Specialized Centers in Algeria: A Qualitative Study in Mila Province - Boudida, Leila (Journal of Ecohumanism, 2026)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder with social communication deficits and restricted or repetitive behaviors . Early and accurate assessment is essential in diagnosing, planning intervention, and providing long-term support for children with ASD. The aim of this study was to investigate assessment practices in the centers of specialization in the Mila Province (Algeria) and to identify the main difficulties faced by professionals during the assessment process.A qualitative, descriptive design was used. The data were collected through semi-structured interviews with seven professionals working with children with ASD in psycho-pedagogical and specialized centers. The data collected were analyzed through thematic analysis.Assessment practices were found to be based on clinical observation, parental interviews and professional experience. Use of standardized diagnostic tools such as ADOS-2 and